Investigation of particle damper on tool vibration during boring process. (2021) - Lawrance, G.; Sam Paul, P.; Moses Jan, N.; Stan Pravin, S.
Abstract: In boring operations, tool vibration is an important factor that affects the production in the manufacturing sector, due to its much overhanging length. An attempt is made to suppress tool vibration effectively by means of a particle damper. A particle damper is offered through particle which dissipates energy through friction and inelastic collisions. A particle damper with variable material, size, and filling in a boring tool is fabricated in this work. A 27 run experiment were conducted to find the effect of particle damping on tool vibration during the boring process. The results were compared without particle damper and found the particle damper suppress tool vibration and cutting force effectively. The particle in the boring tool will collide with one another and increases the rigidity of the tool holder which enhances the cutting parameters.